Early-onset Unilateral Terrien’s Marginal Degeneration - Sohini Mandal; Muskan Garg; Gaurav Sachdeva; Anushka Agarwalla; Prafulla Kumar Maharana (Delhi Journal of Ophthalmology)
Purpose: We aimed to describe the cases that highlight the fact that Terrien’s marginal degeneration (TMD) can present at an early age and should be considered when evaluating young patients with peripheral corneal thinning disorders. Materials and Methods: All cases of early-onset unilateral TMD that presented to a tertiary eye care center were included in the study. Three cases of early-onset unilateral TMD were reviewed. Case 1 (10 years, male) presented with superior arcuate band of corneal stromal thinning extending from 9 to 3 o’clock hours. in the right eye with associated corneal vascularization and lipid deposition at the leading edge of the furrow. Case 2 (14 years, female) presented with a superior crescentic band of corneal stromal thinning extending from 10 to 2 o’clock positions in the left eye. Vascularization of the cornea and lipid deposition were observed at the leading edge of the furrow in this case as well. Case 3 (9 years, male) presented with a superior arcuate band of corneal stromal thinning extending from 10 to 2 o’clock positions in his left eye. Corneal vascularization and lipid deposition were observed at the leading edge of the furrow formation. Results: A preliminary diagnosis of early-onset unilateral TMD was made in all the cases that was subsequently confirmed on Scheimpflug imaging and anterior segment optical coherence tomography. The mean astigmatism of the affected eye was 4.6 ± 2.3 D. All cases were prescribed spectacle correction, which resulted in significant improvement: 6/60-6/24 (Case 1), 6/36-6/9 (Case 2), and 6/18-6/9 (Case 3). Conclusion: A comprehensive case history and meticulous slit-lamp examination are essential, and TMD should be considered a differential diagnosis for peripheral corneal ectatic disorders in childhood.